2018
DOI: 10.1158/1538-7445.am2018-235
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 235: Type 2 diabetes and glycemic traits in relation to colorectal cancer risk: A Mendelian randomization study

Abstract: Background: Although type 2 diabetes (T2D) has been linked to an increased risk of colorectal cancer (CRC), a causal relationship remains to be established. Also, the influence of hyperglycemia and impaired beta-cell function on CRC remains to be determined. Methods: We performed a Mendelian randomization (MR) study using common single nucleotide polymorphisms (SNPs) identified from prior genome-wide association studies for T2D (78 SNPs), fasting glucose (36 SNPs), glycosylated hemoglobin (HbA1c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We identified 165 manuscripts published before 17 October 2019 by use of the following medical subject heading terms and/or text words: "diabetes," "glucose," "insulin," "glycemic," "cancer," "carcinoma," "Mendelian randomization," "Mendelian randomization," "instrumental variable causal inference," "causal inference using instrumental variable," and "causal inference using genetic variants." After title, abstract, and full text screening, seven studies were included in this meta-analysis (28)(29)(30)(31)(32)(33)(34). Details of exclusion criteria are presented in Supplementary Fig.…”
Section: Meta-analysis Of Mr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 165 manuscripts published before 17 October 2019 by use of the following medical subject heading terms and/or text words: "diabetes," "glucose," "insulin," "glycemic," "cancer," "carcinoma," "Mendelian randomization," "Mendelian randomization," "instrumental variable causal inference," "causal inference using instrumental variable," and "causal inference using genetic variants." After title, abstract, and full text screening, seven studies were included in this meta-analysis (28)(29)(30)(31)(32)(33)(34). Details of exclusion criteria are presented in Supplementary Fig.…”
Section: Meta-analysis Of Mr Studiesmentioning
confidence: 99%
“…Meta-analysis of the association of T2DM with certain site-specific cancers. *Effect size in a study by Song et al(34) was estimated in men and women separately. First author names appear for Cancer site & Study column.…”
mentioning
confidence: 99%
“…Adiposity alters the systemic metabolism [18][19][20], but evidence for the effects of adiposity-altered metabolites on CRC is scarce. One MR study suggested that total cholesterol raises CRC risk [21], while others suggested no effect of blood glucose [22] and mixed support for fatty acids [23]. Overall, the scope of metabolic traits examined has also been narrow.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 165 papers published before October 17th, 2019, by use of the following medical subject heading terms and/or text words: "diabetes", "glucose", "insulin", "glycemic", "cancer", "carcinoma", "Mendelian randomization", "Mendelian randomisation", "instrumental variable causal inference", "causal inference using instrumental variable" and "causal inference using genetic variants". After title, abstract and full text screening, seven studies were included in this meta-analysis (28)(29)(30)(31)(32)(33)(34). Details of exclusion criteria is presented in Supplementary Figure 1.…”
Section: Meta-analysis Of Mr Studiesmentioning
confidence: 99%